2015
DOI: 10.1089/aid.2014.0081
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibody Responses to HIV Infection in Ugandan Women Infected with HIV Subtypes A and D

Abstract: We compared the serologic response to HIV infection in Ugandan women with HIV subtype A (N = 82) and D (N = 32) infection using a limiting antigen avidity assay (LAg-Avidity assay); 2,614 samples were analyzed. Study participants were followed a median of 6.6 years after HIV seroconversion. Samples were classified as assay positive if they had a LAg-Avidity assay result < 1.5 normalized optical density units (OD-n). Women with subtype D infection were more likely to have delayed antibody maturation. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…in Asia, where HIV‐1 B, CRF01_AE and many B‐C recombinant forms are observed ). Development and validation of MAAs for use in East African settings may be particularly difficult, since individuals with subtype D infection have been shown to have delayed antibody maturation compared to other subtypes . We previously demonstrated that HIV diversity is a useful biomarker for cross‐sectional incidence estimation .…”
Section: Discussionmentioning
confidence: 99%
“…in Asia, where HIV‐1 B, CRF01_AE and many B‐C recombinant forms are observed ). Development and validation of MAAs for use in East African settings may be particularly difficult, since individuals with subtype D infection have been shown to have delayed antibody maturation compared to other subtypes . We previously demonstrated that HIV diversity is a useful biomarker for cross‐sectional incidence estimation .…”
Section: Discussionmentioning
confidence: 99%
“…Dominate HIV-1 strains in Kenya are clade A virus, which comprise over 50% of HIV infection, and clade D virus which covers roughly 12% to 22% of infections [ 48 – 53 ]. Clade D HIV has shown to have high levels of false-recent misclassification on antibody-based HIV incidence assays due to deferred antibody maturation and rapid antibody decline [ 25 , 26 ]. Previous studies have reported LAg-false-recent rates as high 9% to 16% in clade D HIV compared to 1.3% to 2.7% in clade A HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Long-standing infection was defined as: 1) testing non-recent on LAg or 2) testing recent on LAg and from an HIV-infected person who was taking ART. Because the reported mean duration for recent infection (MDRI) for LAg for predominate HIV-1 subtypes in Kenya varies from 109 days for subtypes A and D infections combined, 172–211 days for subtype A infections, and 273–283 days for subtype D infections [ 24 26 ], for the purposes of this analysis recent infection was presumed to represent HIV infection acquired roughly less than one year prior to specimen collection while long-standing infection was presumed to represent HIV infection acquired roughly one year or greater prior to specimen collection.…”
Section: Methodsmentioning
confidence: 99%
“…Generalized antibody responses to HIV infection, such as antibody titer and avidity, tend to plateau approximately 1 year after HIV infection ( Busch et al, 2010 ). These characteristics of the antibody response are impacted by a variety of factors, including natural and drug-induced viral suppression ( Koenig et al, 2013 ; Wendel et al, 2017 ; Kassanjee et al, 2014 ), disease progression ( Laeyendecker et al, 2012b ), and HIV subtype ( Longosz et al, 2014 , 2015 ). Previous studies evaluating the banding pattern in western blots demonstrate that HIV antibody specificity evolves early in infection ( Fiebig et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%